(untitled) (JOURNAL OF ADVANCES IN AGRICULTURE, 2014)
The experiment was conducted to find out the effect of variety, nitrogen level and harvesting time on yield and seed quality of barley. The treatments used in the experiment consisted of two varieties viz. BARI Barley 4 and BARI Barley 5, three harvesting time viz. 35, 40 and 45 Days after Anthesis (DAA) and nitrogen levels viz. 0, 70, 85 and 100 kg N ha-1 . The experiment was laid out in a spilt- spilt-plot design with three replications assigning the variety to the main plot, harvesting time to the sub-plots and nitrogen level to the sub-sub plots. Variety had significant effects on the all yield attributes except fertile seeds spike-1 . Seed quality parameters viz. normal seeds spike-1 , deformed seeds spike-1 , germination (%) and vigour index were statistically significant. The variety BARI Barley 5 produced higher grain yield and seed quality than BARI Barley 4. Grain yield from BARI Barley 5 and BARI Barley 4 were 4.59 t ha-1 and 4.24 t ha-1 , respectively. Significantly, the highest 1000-seed weight (46.90 g) was produced by BARI Barley 5 than (37.90 g) BARI Barley 4. The result revealed that harvesting time had significant effect on yield and yield attributes and seed quality parameters. Seed yield was highest (4.65 t ha-1 ) when the crop harvested at 40 DAA and it was increased linearly from 35 DAA. Maximum quality seed and 1000-seed weight (43.20 g) was obtained when the crop harvested at 40 DAA. All the yields, yield attributes and seed quality parameters were significantly influenced by nitrogen levels. The highest grain yield (5.14 t ha-1 ) was obtained when BARI Barley 5 variety was fertilized by 100 kg N ha-1 and the lowest (3.14 t ha-1 ) was obtained from control treatments. Normal seeds spike-1 , vigour index, germination (%) were better at 85 kg N ha-1 in variety of BARI Barley 5 than BARI Barley 4. So it can be concluded that BARI Barley 5 showed better result when fertilized with 100 kg N ha-1 and harvested at 40 DAA for getting maximum yield and 85 kg N ha-1 and harvested at 40 DAA for getting better quality seed.